2018
DOI: 10.1007/s00441-018-2858-2
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin system in the hippocampus

Abstract: Among the more than 300 biological actions described for prolactin, its role in the neurogenic capacity of the hippocampus, which increases synaptogenesis and neuronal plasticity, consolidates memory and acts as a neuronal protector against excitotoxicity-effects mediated through its receptors are more recently known. The detection of prolactin in the hippocampus and its receptors, specifically in the Ammon's horn and dentate gyrus, opened up a new field of study on the possible neuroprotective effect of hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Thyroid hormone and GC synergy in regulating growth hormone receptor expression in rodent pituitary cells has actually been reported as early as the 1970s [120] and is one of the well-established processes regulated by both hormone axes [121, 122]. While our results are consistent with the known effect of TH and GC in the hypothalamus and pituitary cells which then consequently affects the timing of development and regulation of body size, prolactin also has specific functions in neurodevelopment and neuroprotection in the hippocampus [123, 124]. For example, prolactin administration exerts a neuroprotective effect on hippocampal neurons in both in vivo and in vitro rodent models of excitotoxicity [125, 126].…”
Section: Discussionsupporting
confidence: 87%
“…Thyroid hormone and GC synergy in regulating growth hormone receptor expression in rodent pituitary cells has actually been reported as early as the 1970s [120] and is one of the well-established processes regulated by both hormone axes [121, 122]. While our results are consistent with the known effect of TH and GC in the hypothalamus and pituitary cells which then consequently affects the timing of development and regulation of body size, prolactin also has specific functions in neurodevelopment and neuroprotection in the hippocampus [123, 124]. For example, prolactin administration exerts a neuroprotective effect on hippocampal neurons in both in vivo and in vitro rodent models of excitotoxicity [125, 126].…”
Section: Discussionsupporting
confidence: 87%
“…Another hormone that raises its levels in the post‐pregnancy stage is prolactin, whose receptors are located in the PFC and the hippocampus, among others (Bakowska & Morrell, ; Cabrera‐Reyes, Vergara‐Castañeda, Rivero‐Segura, & Cerbón, ). Recent studies have also suggested that this hormone may improve cognition and play a neuroprotective role, showing an increase in the density of dendritic spines in the PFC and CA1 of the hippocampus during lactation (Carretero et al, ; Chen et al, ; Salmaso, Quinlan, Brake, & Woodside, ). However, to know if this hormone participates in the changes described in the present work, it is necessary to study only the effect of pregnancy without lactation to resolve this question.…”
Section: Discussionmentioning
confidence: 99%
“…Like progesterone, the link between plasma prolactin and the hippocampus has not been properly investigated in humans. While there is a large body of work suggesting that prolactin can impact the rodent hippocampus at the cellular level (Cabrera-Reyes et al, 2017; Carretero et al, 2018; Morales et al, 2014), this does not appear to translate to any change in whole hippocampal volume (Torner et al, 2009). There is evidence from animal and cellular models that reproductive hormones can influence the hippocampus at the cellular level through changes in AHN, cell survival or branching (Chan et al, 2014; Morales et al, 2014; Ransome and Boon, 2015), therefore it is possible that this may also occur in humans without affecting whole hippocampal volume.…”
Section: Discussionmentioning
confidence: 99%